Crk and CrkL are required for cell transformation by v‐fos and v‐ras. Issue 1 (3rd January 2015) - Koptyra, Mateusz; Park, Tae‐Ju; Curran, Tom
Abstract : Crk and CrkL are SH2‐ and SH3‐containing cytosolic adaptor proteins that can induce anchorage‐independent growth of fibroblasts. Crk and CrkL play key roles in maintaining cytoskeletal integrity, cell motility and migration. We investigated the role of these two proteins in oncogenic transformation induced by v‐ fos and v‐ ras oncogenes using cell lines and fibroblasts carrying conditional alleles of Crk or CrkL. Transformation was assessed by cell morphology, saturation density and anchorage‐independent growth in soft agar. We found that cell lines expressing v‐ fos or v‐ ras in the absence of Crk or CrkL displayed no evident morphological alterations and reduced anchorage‐independent growth compared to those retaining Crk and CrkL. Similarly, overexpression of v‐ fos in mouse embryonic fibroblasts conferred a growth advantage and induced morphological changes, both of which were abrogated in the absence of either Crk or CrkL. In contrast, Crk, but not CrkL, contributed to v‐ ras ‐induced transformation of embryonic fibroblasts. These results suggest that both Crk and CrkL are required for the acquisition of cellular transformation by v‐ fos, whereas Crk plays a more prominent role than CrkL in v‐ ras ‐induced transformation. © 2015 Wiley Periodicals, Inc.